The effect of key financial ratios to share return in the companies listed on lq45 index indonesian stock exchange (idx) - Anggraeni Novianti, Dwi; Murtaqi, Isrochmani (The Indonesian Journal of Business Administration, 2019)
Abstract. The capital market is an important part for the economy of a country. Jakarta Composite Index (JCI) reflected that Indonesia stock market is growing rapidly in the number of investors, amount of transactions and market capitalization. Indonesian Stock Exchange (IDX) continues to grow more quickly than the majority of markets in developed and developing economies – not just in Asia, but in around the world. This study research has conducted regression analysis to determine the relationship between share return and selected financial ratios namely Earning Per Share (EPS), Price Earning Ratio (PER), Price to Book Value (PBV), Debt to Equity Ratio (DER), Net Profit Margin (NPM) and Return on Equity (ROE) of companies listed as LQ45 in Indonesia Stock Exchange for the period of 2013 – 2017. Data used in this research is secondary data. Samples are from 19 companies listed in LQ45 Index. This study confirm that DER, NPM, EPS, PER and PBV individually have positive significant effect on the Share Return and ROE has negative significant effect on the Share Return. Likewise DER, NPM, ROE, EPS, PER and PBV are simultaneously influence the Share Return.Keywords: Regression analysis, panel data, financial ratios, share return